Is there a secular trend regarding puberty in children with down syndrome? - Erdoğan, Furkan; Güven, Ayla (Frontiers in Endocrinology, 2022)
Introduction There are very few studies on the age of onset and end of puberty in children with Down syndrome (DS). Also, data regarding the course of puberty in these children compared to their healthy peers is limited. Moreover, there is limited information regarding the effects of factors such as obesity and hypothyroidism on the puberty process in children with DS. Our aim in our study is to determine whether the pubertal development of children with DS differs from their healthy peers and from previous studies conducted with DS children. Methods The medical records of DS children were examined retrospectively. The anthropometric measurements and the age of onset of pubertal stages, and menarche were recorded. The patients’ age at puberty onset, the puberty processes, and age at menarche were compared with their healthy peers and previously published data on children with DS. Results Of the 140 Down syndrome patients followed in our clinic, 51 of whom with puberty constituted the study group. The mean age of onset of puberty was 10.3 ± 1.0 years in our group (10.0 ± 0.8 years for girls, 10.6 ± 1.2 years for boys, respectively). Obesity occurred in 46% of pubertal girls with DS. The age of menarche in girls with DS was 11.8 ± 0.7 years. The menarche age of girls with DS was significantly different from healthy girls. In the DS boys, only the Tanner V stage ages were different from the healthy children. True- precocious-puberty was detected in three children. Conclusion Although breast development begins later in females with DS than in their healthy peers; menarche is detected earlier than in their peers and a tendency towards obesity in the whole population. While the age of pubertal onset was similar to healthy children in male patients, our findings suggest that their puberty duration is longer.